The Influence of The Scientific Learning Approach Assisted by Froggy Jumps on The Indonesia Language Learning Outcomes of Grade IV Elementary School Students - Nur Aswina, anna nur aswina; Arafat, Yasir; Faipri Selegi, Susanti (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
The purpose of this study was “to determine the influence of the Scientific Learning Approach assisted by Froggy Jumps on the learning outcomes of Indonesian language of grade IV students of SD Negeri 09 Makarti Jaya”. The methode used in this study was Pre-experimental with a One-Group Pretest-Posttest design. The population and sample of this study were all grade IV students at SD Negeri 09 Makarti Jaya with a total of 17 students. The data collection was carried out using tests in the form of Pretest and Posttest. The result showed that the average result of the initial Pretest test score 50.35 and the average result of the final Posttest test score 86.70. The result of the hypothesis test showed a t count value 3.303 and a t table value of 2.131 (t count > t table) so that Ho was rejected and Ha was accepted. It can be concluded that there is an influence of the Scientific Learning Approach assisted by Froggy Jumps on the learning outcomes of Indonesian language of grade IV students of SD Negeri 09 Makarti Jaya.